A importância da “governança corporativa e estratégia comercial” em cenário de crise econômica - estudo de caso da MRV - Santos, Wanderley Santana dos (2019)
The present study aims to investigate the extent to which the adoption of the Corporate Governance principles, as well as targeted and timely business strategies, contribute to the maintenance of satisfactory accounting and financial performance of companies operating in sectors very sensitive to the occurrence of events. adverse systemic impacts resulting from corruption scandals and economic crises. This research was intentionally directed to the construction sector, commonly considered among the main activity segments to be impacted by economic crises and, more recently, to be linked to the announcement of corruption scandals by the media. Among the companies in the sector, the company MRV Participances S. A. was selected, which has the formation of its operating revenue mainly linked to contracts with the Federal Government, through the "Minha Casa, Minha Vida" Program. Given this context, one could intuitively admit the company's greater exposure to corruption scandals. As no evidence of this intuition was confirmed in the selected materials, it was assumed that, in part, the maintenance of satisfactory financial and accounting indicators, even in crisis scenarios, was due to the commitment to the principles of Corporate Governance and commercial strategy. highly prospective sector, due to the high housing deficit for low-income social classes